Till death do us part - Flynn, Laurie Elizabeth (New York : Simon & Schuster, 2024)
"Ten years ago, June's beloved husband drowned on their honeymoon, his body never found. Now, a decade later, June is finally ready to move on. She owns a natural wine bar in Brooklyn and is engaged to a patient, supportive man named Kyle. She's excited to finally begin a new chapter in her life and start a family. But out of the blue, she sees him--Josh, her first husband. Is this just a hallucination from the guilt June carries about finally moving on, or is it possible that her husband never died in the first place? June tries to forget about this vision, chalking it up to grief and nerves, but soon enough, she stumbles across a website for a winery in Napa, and the owner in the photo is identical to her dead husband. With her upcoming wedding looming and a fiancé who's already worried she hasn't quite left her past behind, June secretly flies to Napa for answers. But she's not prepared for all the secrets she's about to unlock because everything she thought she knew about her first love is a lie"--
Keywords: Women -- Fiction; Wineries -- Fiction; Missing persons -- Fiction; Man-woman relationships -- Fiction; Spouses -- Fiction; Secrecy -- Fiction; Napa Valley (Calif.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Novels